DUKUNGAN PASANGAN DAN PANDANGAN NILAI ANAK LAKI-LAKI DALAM KEIKUTSERTAAN VASEKTOMI FAMILY SUPPORT AND THE VALUE OF BOYS IN VASECTOMY PARTICIPATION: Family Support And The Value Of Boys In Vasectomy Participation - Aulia, Fika Aulia (LPPM - STIKES Pemkab Jombang, 2023)
The number of male participation in Indonesia has decreased from 0.3% in 2012 to 0.1% (IDHS, 2017).The addition of the number of male participation in becoming vasectomy acceptors in Banjarmasin City during 2020 was still small, namely 8 acceptors. The low participation of men has a negative impact on the success of the family planning program. In advancing the male family planning program, especially vasectomy, the role of partner support is very necessary because it can affect the husband's motivation and desire to become a vasectomy acceptor. Boys in Indonesia are still considered to be of a higher than girls. families have not stopped give birth because they don’t have son yet. The purpose of this study was to determine the relationship between partner support and vasectomy family planning participation. The method in this study is a type of descriptive analytic research with sampling using accidental sampling technique with the Mann Whitney statistical test. The conclusion of this study is that there is a relationship between family support, value of boys and male participation in using vasectomy.